A Shrinking Space for Civil Society? A Conference on Civil Society and Europe's Political Culture: Wrocław, Poland, October 2016 - Domaradzka-Widła, Anna; Kavelashvili, Nino; Markus, Eszter; Sälhoff, Philipp; Skóra, Maria (2016)
Abstract: Contents: 1. Philipp Sälhoff and Maria Skóra: Dialogue on Europe - Rebuilding Trust and Redefining Europe in Tough Times; 2. Nino Kavelashvili: Conference Report; 3. Anna Domaradzka: Mapping Civil Society in the Visegrád Countries; 4. Eszter Markus: Shrinking Space for Civil Society in the Heart of Europe; 5. Rupert Strachwitz: Postscript